A Proposed Approach for Evaluating Soils Optimum Moisture Content Arithmetically and Use Statistical Functions for Checking Method - sadiq yasun, Azhar; N. Al Abbasi, Jamal (International Journal of Engineering and Technology, 2018)
The processing of optimum moisture  content for specific soils as indicated by ASTM D698 specifications detail relies upon developing the fitting third or second degree bend connection between dampness content versus soil dry unit weight on a fitting bend, the registered optimum moisture  substance may contrast for a similar soil as for fitting bend figure and its position. The main objective of this study is to evaluate the optimum moisture content value based on computing average moisture content adapted from standard or modified Proctor compaction test trials and compared it with respect to the computing optimum moisture content using standard method. The research deals with a (52) compaction tests results with a wide range of optimum moisture content and dry unit weight to explore the relationships between them. The study also explores the maximum dry density values which versus standard optimum moisture content and average adopted moisture content. Statistical part depends on evaluating many statistical function values for standard and research method starts by evaluating significance of normality using Kolmogorov-Smirnov test. The average differences between standard optimum moisture content and an average value (this study depends) for moisture content was about (-0.20) and an average of differences for dry unit weight values was (0.261).